An Analytical Method to Test Elastic Rock Mass Parameters Based on a Macro-Joint Model - Dong, Junting; Fu, Yuhua; Wang, Guanshi (Frontiers in Physics, 2021)
The measurement of rock joint parameters is a hot and difficult problem in rock mechanics. Joints have great influence on the propagation of stress wave in rock mass. Since the multiple transmission and reflection effects of stress waves propagating at the joint interface have not been considered, the existing displacement discontinuity model cannot obtain an accurate waveformofreflection wave. The joint is regarded as a rock layer in this paper, and the transmission and reflection laws of stress waves are analyzed. The same type of stress waves are superimposed, and an analytical model of the stress wave passing through a single joint layer is established. By extending the single joint layer analysis model, the analysis model of stress waves propagating through group parallel strata can be obtained. Taking a single joint layer as an example, a measuring line is arranged in the normal direction of the joint, and two measuring points on both sides of the joint are arranged on the line to record the waveforms of the incident and transmitted waves. Comparing the calculated waveform of the incident wave with the measured waveform of the incident wave, the elastic parameters of joints can be obtained. Finally, six tests were carried out on a joint with a thickness of 0.04 m with consistent test results being obtained, indicating that the test method has good stability.